ANALYSIS OF SUGAR, SALT AND FAT IN SNACK FOODS SOLD AT ELEMENTARY SCHOOL FOOD STALLS - Zaizafia, Athaya; Aristi, Dela; Ciptaningtyas, Ratri; Angkasa, Dudung (Journal of Nutrition College, 2024)
ABSTRACTBackground: Snacking is common among elementary school-age children. Ironically, snacks often contain lots of sugar, salt, and fat (SSF) which mostly available at school's area and might contributed to poor dietary pattern. Objective: to determine SSF’s content among snack food (SF) at school food stalls and intake of SSF from the SF among school-age children. Methods: This cross sectional study involved eighty-nine children age 8 to 12 at Madrasah Pembangunan elementary school in South Tangerang city  that randomly selected. Street food was classified as main dish, snacks and drinks. SSF content was determined by desk analysis through conversion of raw-cooked food, edible portion, estimated of intake sugar, salt and oil absorption from actual food weighing of listed snack foods. Intake of SSF was obtained from two non-consecutives 24 hours food recalls. FoodWorks and SPSS software were used to analyze food and descriptive analysis, respectively. Results: We found that almost one third of subjects experienced overweight (12.4%) and obesity (16.9%). There were 53 items of hawker foods were identified within school area and were comprised from 18 main dishes, 35 snacks and 10 drinks. Snack food contains more SSF content compared to main dishes. Salt is the highest contribution (120%) to recommended daily allowance compared to sugar and fat.Conclusion: The percentage contribution of snacks in school-age children consumption needs to be highlighted as an alarming wake-up call to introduce nutrition labelling on snacks sold at school areas.Keywords : snack food; sugar; salt; fat; school children ABSTRAKLatar belakang: Ngemil merupakan hal yang umum di kalangan anak usia sekolah dasar. Ironisnya, jajanan seringkali mengandung banyak gula, garam, dan lemak (GGL) yang banyak terdapat di lingkungan sekolah dan dapat menyebabkan pola makan yang buruk. Tujuan: untuk mengetahui kandungan GGL pada makanan jajanan di sekolah dan asupan GGL dari makanan jajanan pada anak sekolah. Metode: Studi cross sectional ini melibatkan delapan puluh sembilan anak usia 8 hingga 12 tahun yang dipilih secara acak. Makanan jalanan diklasifikasikan sebagai hidangan utama, makanan ringan dan minuman. Kandungan GGL ditentukan dengan analisis tabel melalui konversi makanan mentah, porsi yang dapat dimakan, perkiraan asupan gula, garam dan penyerapan minyak dari makanan aktual yang ditimbang dari makanan ringan yang terdaftar. Asupan GGL diperoleh dari dua penarikan makanan 24 jam non-berturut-turut. Perangkat lunak FoodWorks dan SPSS masing-masing digunakan untuk menganalisis makanan dan analisis deskriptif. Hasil: Hasil studi mendapatkan sepertiga anak sekolah responden kami mengalami kelebihan berat badan (12.4%) dan obesitas (16.9%). Teridentifikasi 53 jenis makanan jajanan di lingkungan sekolah yang terdiri dari 18 makanan utama, 35 makanan ringan dan 10 minuman. Makanan ringan mengandung lebih banyak kandungan GGL dibandingkan dengan makanan utama. Kontribusi garam dalam makanan ringan bahkan mecapai 120% dari angka kecukupan gizi , angka ini lebih tinggi dari persentase gula dan lemak.Kesimpulan: Persentase kontribusi GGL dari makanan ringan yang dikonsumsi anak sekolah perlu diawasi sebagai peringatan dini untuk memperkenalkan label gizi pada makanan jajanan yang dijual di lingkungan sekolah.Kata Kunci : camilan; gula; garam; lemak; anak sekolah